(3QSGdI aj GdYQT hGdcQSjs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC fhQkG eMLhfkG edjJg bjdkG adeG CTQa ajg GSJYed LdGjG ef cd TF Edj CeO GdMb s
(3BNQgG (B:s
(3heG YdjgeG eG jSJfHM dfG GdLh heG ajg hGdHQ hGdHMQ heG ajgeG hEf de jSeY cdGefG s
(3Vef eLehY , JQJjHgG (B: 10s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs